Craniofacial fractures sustained under the influence of alcohol: what are the differences between the sexes? - Thorén, Hanna; Virtanen, Klaus; Oksanen, Erkka; Toivari, Miika; Suominen, Auli; Puolakkainen, Tero; Snäll, Johanna (Medical Journal Sweden AB, 2025)
Objective: To identify mechanisms and types of injuries in patients having sustained craniofacial fractures under the influence of alcohol, and to compare the frequencies of them between males and females.
Materials and methods: Patients included were adults who had been diagnosed with craniofacial fracunder the influence of alcohol at the time of injury. The primary outcome variables were assault-related and fall-related injury mechanisms. The secondary outcome variables were other injury mechanisms, time of accident, type of craniofacial fracture and severity of facial fracture. The primary predictor variable was sex. The control variable was age at the time of injury. The statistical modelling was executed using logistic regression.
Results: Of the total of 2,859 patients with craniofacial fractures, 1,014 patients (35.5%) fulfilled the inclusion criteria. Males predominated (84.6%). Assault (38.0%) was the most frequent aetiology. Compared to the odds of females, males had 2.8 times greater odds for assault, 2.4 times greater odds for isolated cranial fracture and 1.7 times greater odds for a facial injury severity score of >= 3. Females had 2.0 times greater odds for any fall compared to the odds of males.
Conclusions: Particularly male patients are frequently under the influence of alcohol at the time of injury, predisposing them to assault and severe facial fractures more often than females. Codes of practice on how to identify unhealthy alcohol use and how to intervene are recommended.